STRATEGI PENGUATAN KEMANDIRIAN BLUD-SMK MELALUI PENDAMPINGAN PENYUSUNAN RANCANGAN PERATURAN GUBERNUR MENGENAI TARIF PRODUK SMKN DI SUMATERA BARAT - Sanda Patrisia Komalasari; Rayna Kartika; Silmi Silmi; Fitriyeni Oktavia (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
This service activity aims to increase financial independence and provide clear tariff standards for the Regional Public Service Agency (BLUD) of State Vocational High Schools (SMKN) in West Sumatra in setting tariffs for the products they produce. To create standardization, the government needs to set tariff rules for products provided by SMKs. Academic involvement is necessary for tariff determination according to applicable calculation rules. To create standardization, the government needs to set tariff rules for products provided by SMKs. Academic involvement is necessary for tariff determination according to applicable calculation rules. The method of this service activity is in the form of a mentoring workshop for 43 representatives of SMKN in West Sumatra. The West Sumatra Education Service held this activity at the ZHM Padang Hotel. In this activity, the Andalas University Accounting Lecturer was trusted as a resource person who accompanied and prepared the tariff calculation formula that SMKN will use in West Sumatra. The activity was carried out over two days, 7-8 November 2023. During the activity, the team from Andalas University guided the activity participants to calculate the rates for several products they had produced. Before the workshop, the team held an online meeting with participants to determine the data that needed to be prepared for calculating tariffs. The output of this activity is an attached formula and example of calculating tariffs for SMKN Regional Public Service Agency (BLUD) products, which are connected to the West Sumatra Governor's Regulation.